Women-mothers who work. The resignification of motherhood in female professionals in Guadalajara-Mexico - Castañeda-Rentería, Liliana Ibeth (2019)
The purpose of this article is to analyze the resignifications of motherhood among female professionals with children residing in Guadalajara, Mexico. We argue that the transformations of the representation of motherhood and of the mother—like sociocultural institutions—are promoted and suffered by those women who “want everything”, that is, those who do not give up their professional projects, and neither give up their reproductive capacities which they conceive as part of what being a woman means to them. To account for the above, we analyzed four biographical interviews conducted with the life story technique. The results show the tensions, conflicts and guilt experienced by the professional women who work and who are mothers, as well as the way in which they experience at the same time feelings of personal self-affirmation and feelings of pride.